The Potential of Online Platforms Compared to In-Person Teaching - Different Experiences of Teachers - Danijela N. Vasilijević; Žana P. Bojović; Marina Ž. Semiz (University of Belgrade, Teacher Education Faculty, 2022)
The first part of this paper offers a theoretical interpretation of the previous research of the methodological potential and efficiency of online teaching (especially during the Covid regime), whereas the second part is methodologically oriented towards the examination of the attitudes of teachers on the potential of the implemented distance learning platforms vs. in-person teaching. The sample is represented by 604 teachers of elementary and secondary schools from all administrative regions in the Republic of Serbia. The research was performed using descriptive method and the survey method. The results of the research showed that: a) teachers mostly do not have a positive perception of the advantages of distance learning platforms compared to traditional, in-person teaching with regards to the application of teaching technology; b) traditional teaching is considered more efficient for the quality of work of students and teachers; c) teachers do not show the expected willingness for the occasional use of the hybrid model in the future; the independent variables did not influence the final results of the research. A statistically significant difference was observed only in the attitudes of teachers of different educational cycles and the users of different learning platforms.